Effect of overlap support characteristics on peel strength of weld-bonded joints. (2019) - Ameen, Wadea; Alsamhan, A.M.; Darwish, S.M.
Bonded joints normally have a low peel tensile strength, since the stresses are concentrated on the small bond line. It has been proposed that adding a weld-bonded overlap support to the T-peel joint will enhance its peel strength tremendously. Since this support may increase the weight of the joint, a trade-off between weight increase (material type and thickness) and improved peel strength must be made. The aim of the present work is to investigate the effect of the overlap support characteristics (material and thickness) on the stress distribution of the T-peel joint. Different materials with different thicknesses are considered in order to strengthen the T-peel joint. A finite element technique was used for evaluating the current models. The results showed that the peak stress decreases with increasing thickness and stiffness of the overlap support.